FINANCIAL GOVERNANCE OF BOGOR DISTRICT LOCAL GOVERNMENT IN THE PERSPECTIVE OF PUBLIC ACCOUNTABILITY AND PUBLIC CHOICE THEORY: - - Aulia, Dea Fitri; Sumaryana, Asep; Pancasilawan, Ramadan (DIA: Jurnal Administrasi Publik, 2025)
To discuss and analyze the financial management of the local government of Bogor Regency using the concept of public accountability and public choice theory is the purpose of this paper. Furthermore, this writing is to see how the local government of Bogor Regency can be accountable in the process of managing its regional finances which is expected to be more efficient and effective so that the administration of government can be carried out properly (good governance). Qualitative descriptive research methods are used in this study, by applying Mueller's theory of public choice and Ellwood's concept of public accountability which includes; legal accountability and honesty, managerial accountability, program accountability, policy accountability and financial accountability. The results of the study show that the Bogor Regency Regional Government has mostly implemented legal accountability and honesty, managerial, programmatic, policy and financial systems. Financial management is carried out by adhering to the provisions of applicable regulations and prioritizing the principles of transparency and integrity through various mechanisms such as training, job rotation, online application on the website and periodic financial reporting. However, there are still a number of obstacles, especially related to the limitations of human resources (HR) and budgets, policy changes and obstacles, which affect the implementation of policies and optimal financial management.